Observation of Sb2S3-type post-post-perovskite in NaFeF3. Implications for ABX3 and A2X3 systems at ultrahigh pressure - Serena Margadonna (Mineralogical Magazine, 2016)
Ten years have passed since the description of the perovskite to post-perovskite transition in MgSiO3 and its’ impact on the mineralogy and rheology of the D’’ region at the base of the Earth’s mantle. Much work has explored the mechanisms operating during this transformation and their influence on seismic response. In parallel, calculations in ABX3 systems have identified potential structures for a denser post-post-perovskite phase occurring at higher pressures. However, experiments have yet to elucidate any higher pressure form, beyond the CaIrO3-type. Here we describe the structures and transformations that lead to the crystallisation of a post-post-perovskite of Sb2S3-type in a GdFeO3-type fluoroperovskite at high pressure conditions. The use of single-crystal techniques gives unique access to the relative crystallographic orientations of all polymorphs. We use this information to extend this description to include other calculated and observed forms that are competitive in ABX3 and A2X3 stoichiometries (e.g. Sb2S3, -Gd2S3, Be3N2,) and provide substantial information on inter-relationships between these structures. Such information is critical to the interpretation of transition mechanisms, predicting transition sequences and to the expression of directional properties in those transformed structures.